Abdominal stretching to reduce premenstrual syndrome: a case series - Rohmah, Yuni Khoiriyatul Mujtahidah; Mukhoirotin, Mukhoirotin (MEDISAINS, 2020)
Background: cases of premenstrual syndrome (PMS) among teenagers living in Hurun Inn Boarding School at the Pondok Pesantren Darul 'Ulum Jombang are quite a lot. In the 60 teenagers get surveyed, there were 22 (36.67%) people who experienced PMS. It means the problems need acute treatment to overcome.Case presentation: This case study reports the effectiveness of giving abdominal stretching to ten teenagers who have PMS at the boarding school. The results showed a decrease in the PMS scale from a severed level (70%) to a medium-scale (60%) in the first cycle of menstruation and a mild level (60%) in the second cycle.Conclusion: Abdominal stretching can reduce PMS symptoms.